Parental knowledge and attitudes toward childhood vaccination in Konya, Türkiye: a cross-sectional study - Hasan Alper Karakoç; Funda Gökgöz Durmaz (Discover Public Health)
Abstract Aim This study aims to assess parental attitudes toward childhood vaccination and examine their association with sociodemographic characteristics and vaccine-related knowledge. Materials and methods The study was conducted between May 2023, and July 2023, with 400 parents who visited the Pediatric outpatient Clinic and agreed to participate the study. Participants were administered the Sociodemographic Questionnaire, which included questions assessing knowledge about vaccination, as well as the PAVC scale, which evaluates parental attitudes toward childhood vaccinations. The responses were collected through face-to-face interviews with the participants. Data analysis was performed using SPSS22.0, considering p-values < 0.05 as statistically significant. Results A total of 400 parents aged 18–50 participated in the study, with a mean age of 31.6 ± 0.29 years. Of the participants, 78.3% (n = 313) were female. Of participants 5.8% (n = 23) believed that vaccines were unnecessary. Of the participants 15% (n = 60) reported having their child receive a non-routine vaccines. Vaccine hesitancy was observed in 27.5% (n = 110) of participants. There was a significantly negative correlation between the total scores of the Vaccine Knowledge Scale and the PACV scale. Higher education levels, nuclear family structure, and reliance on doctors as a source of vaccine information were associated with higher vaccine knowledge scores and lower vaccine hesitancy scores. Conclusion Vaccine hesitancy was observed in 27.5% (n = 110) of participants. As knowledge about vaccines increased, vaccine hesitancy decreased. Considering these findings, it is crucial to address vaccine hesitancy by enhancing education for healthcare professionals, increasing accurate and up-to-date information on platforms such as social media, the internet, television, and implementing initiatives to raise parental knowledge and awareness about vaccines.